Cognitive functioning associated with stimulant use in patients with non-affective psychosis, their unaffected siblings and healthy controls. Issue 9 (22nd November 2013) - van der Meer, F. J.; Meijer, J. H.; Meijer, C. J.; van den Brink, W.; Velthorst, E.
Abstract : Background: Little is known about the effect of stimulant use (amphetamines, cocaine, ecstasy) on cognitive functioning in schizophrenia patients. The current study examined (1) whether recency and frequency of stimulant use is associated with cognitive functioning and (2) whether these associations differ between psychotic patients, their unaffected siblings and controls. Method: Participants completed a comprehensive cognitive test battery. Stimulant use was assessed by urinalysis and by the Composite International Diagnostic Interview (CIDI). Using random effects regression models, the main effects of Stimulant Use and the interaction with Diagnostic Status on cognitive functioning were assessed. Results: The interaction term between Stimulant Use and Diagnostic Status was not significant for any of the cognitive outcome variables, indicating similar effects of stimulant use in all three groups. Recent stimulant users showed more errors deficit in verbal learning in comparison to never users (Cohen's d  = −0.60, p  < 0.005). Lifetime frequent stimulant use was significantly associated with worse immediate and delayed verbal recall, working memory and acquired knowledge (Cohen's d  = −0.22 to −0.29, p  < 0.005). Lifetime infrequent stimulant use was not associated with significant cognitive alterations in comparison to never use. Conclusions: The presence of cognitive deficits associated with lifetime stimulant use is dependent on the frequency of use, with no observed deficits in infrequent users and modest negative effects in frequent users.